2019
DOI: 10.1136/tsaco-2019-000321
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of isoform-specific and non-selective histone deacetylase inhibitors in attenuating the intestinal damage after hemorrhagic shock

Abstract: BackgroundIsoform-specific histone deacetylase inhibitors (HDACIs) MC1568 and ACY1083 are comparable to the non-selective HDACI valproic acid (VPA) in improving survival in rodents undergoing lethal hemorrhage. However, the organ-specific properties of isoform-specific HDACIs have not been fully evaluated. Also, whether they can act synergistically is not known. We hypothesized that isoform-specific HDACIs are superior to VPA in attenuating intestinal injury and act synergistically when coadministered.MethodsS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Relevant to the latter, various groups have focused on developing cofactor analogs to modulate activities of epigenetic enzymes overexpressed in tumors (15). These studies have identified several promising cellpermeable small molecule inhibitors of histone-modifying enzymes, such as DOT1Li, EPZ004777, LSD1i, and GSK690 (18)(19)(20)(21)(22). However, some cell-permeable inhibitors with high potency in vitro have shown little or no biological activity in vivo (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…Relevant to the latter, various groups have focused on developing cofactor analogs to modulate activities of epigenetic enzymes overexpressed in tumors (15). These studies have identified several promising cellpermeable small molecule inhibitors of histone-modifying enzymes, such as DOT1Li, EPZ004777, LSD1i, and GSK690 (18)(19)(20)(21)(22). However, some cell-permeable inhibitors with high potency in vitro have shown little or no biological activity in vivo (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that class I HDACi MS275 reduces neuroinflammation in a mouse model of Alzheimer’s disease [55][56][57] and suppresses cytokine expression in murine microglia activated with LPS [43]. Although several pieces of evidence reported the MC1568 ability to modulate inflammation according to the cell types [58][59][60], to the best of our knowledge, other than our data, there is no evidence of MC1568’s ability to modulate the glial inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the small samples, differences in survival were found, although the differences among sirtinol, MS-275, LMK-235, tubastatin A, and TSA treatments were not significant. Second, only male rats were used in this study, but this was because there is gender dimorphism in trauma patients (5,9,34), and female sex hormones are considered protective in shock. Future research will need to validate the effect of various HDACIs in female animals.…”
Section: Discussionmentioning
confidence: 99%
“…Histone deacetylases (HDACs) are involved in epigenetic regulation and lead to gene transcription repression. However, HDAC inhibitors (HDACIs) can improve the acetylation of histones to induce transcriptional activation, resulting in the production of proteins (4,5). Acetylation affects the function of several cytoplasmic proteins and leads to a "prosurvival phenotype" (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation